Determining eyeball surface area directly exposed to the effects of external factors. Issue 2 (2nd April 2016) - Juliszewski, Tadeusz; Kadłuczka, Filip; Kiełbasa, Paweł
Abstract : This article discusses determining the surface area of eyeballs of men and women exposed to the direct effects of external factors in the working environment. For one eye, the mean surface is 172–182 mm 2 . The determined surface area can be used in formulas for calculating the exposure of eyeballs to harmful chemical substances in workplace air.